Analysis of Planning, Control, and Evaluation of Financial Management on the Routine Expenditure Budget - Silvia Hendrayanti; Achmad Junaidi; Wanuri Wanuri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Financial management in the public sector, especially at the village level, often faces various challenges. These challenges include limited resources, complexity of administrative procedures, and the need for high transparency and accountability. In this context, the analysis of planning, control, and evaluation of financial management becomes very relevant. This study aims to find out (1) The Influence of Planning on the Routine Expenditure Budget (2) The Effect of Control on the Routine Budget. (3) The Effect of Financial Management Evaluation on Routine Expenditure Budget at Kalisegoro Village Office, Gunungpati District, Semarang City. This research was conducted using quantitative analysis methods. The data is in the form of a list of budget uses of the Kalisegoro Village Office. Data collection through documentation related to the problem being researched at the Kalisegoro Village Office, Gunungpati District, Semarang City. The analysis tool used was multiple linear regression. The results of the study show that Planning and Control has a significant influence on the Routine Expenditure Budget while the Financial Management Evaluation has no effect on the Routine Budget. For further research, it is recommended to use other variables that affect the Routine Expenditure Budget that is not yet present in this study, extend the observation time, and increase the number of samples.